2016
DOI: 10.4049/jimmunol.1502039
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T Cell–Dependent and –Independent Mechanisms of Immune Suppression by CD28/B7 and CD40/CD40L Costimulation Blockade

Abstract: Blocking of costimulatory CD28/B7 and CD40/CD40L interactions is an experimental approach to immune suppression and tolerance induction. We previously reported that administration of a combination of CTLA-4Ig and MR1 (anti-CD40L mAb) for blockade of these interactions induces tolerance in a fully mismatched allogeneic splenocyte transfer model in mice. We now used this model to study whether regulatory T cells (Tregs) contribute to immune suppression and why both pathways have to be blocked simultaneously. Mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 34 publications
0
13
1
Order By: Relevance
“…The frequency of OTII cells was significantly lower in the MR1-treated group compared to the isotype-matched control treated group on days 7 and 14 post-HOD transfusion (Figure 4 A). Given prior studies of MR1 and Tregs in graft-versus-host disease (GVHD) models ( 39 ), we evaluated these cells in our transfused animals. We found no significant differences in the number of endogenous or antigen-specific (CD45.1 + OTII) Foxp3 + CD4 + Tregs between groups (Figure 4 B), with there being extremely few antigen-specific OTII cells to characterize in animals treated with MR1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency of OTII cells was significantly lower in the MR1-treated group compared to the isotype-matched control treated group on days 7 and 14 post-HOD transfusion (Figure 4 A). Given prior studies of MR1 and Tregs in graft-versus-host disease (GVHD) models ( 39 ), we evaluated these cells in our transfused animals. We found no significant differences in the number of endogenous or antigen-specific (CD45.1 + OTII) Foxp3 + CD4 + Tregs between groups (Figure 4 B), with there being extremely few antigen-specific OTII cells to characterize in animals treated with MR1.…”
Section: Resultsmentioning
confidence: 99%
“…The fact that an adjuvant is required in this model for a humoral immune response to occur, in combination with the fact that CD4 depletion or CD40L blockade can induce complete and long-lasting immune tolerance in an antigen-specific manner, suggest but do not conclusively confirm that immune responses to antigens on transfused RBCs are distinct from those to other antigens administered in a soluble form or through different routes. For example, although CD40L blockade has been shown to decrease skin and organ transplant rejection in mice and in non-human primates, suppression of the recipient CD8 + T-cell component of transplant rejection may require additional co-stimulatory molecule blockade or immunosuppression ( 39 , 41 , 42 ). Further, although CD40L blockade has been shown to prevent a primary immune response to factor VIII exposure in murine models of hemophilia ( 43 ), this non-responsiveness does not equate to long-lasting tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate in detail how LGALS1 was involved in the GBM immunosuppressive microenvironment, we undertook big data analysis and evaluated the immunosuppressive cytokines known to be tightly associated with immunosuppressive microenvironment. LGASL1 was positively associated with immunosuppressive genes: LGALS3 , impairing function of human CD4 and CD8 tumour‐infiltrating lymphocytes, SWAP70 restricting spontaneous maturation of dendritic cells (DCs), CHI3L1 secreted by M2 macrophages promoting gastric and breast cancer metastasis, CCL2, SERPING1 inhibiting activation of the complement system, ANXA1 regulating TGF‐β signalling and promoting metastasis formation of basal‐like breast cancer cells, SHC1 promoting breast cancer immune suppression through STAT1 and STAT3, TIMP1 having a liner relationship with CD11b + Gr1+ myeloid cells and CD4 + CD25 + FOXP3+ Tregs, ICAM1 critical for mesenchymal stem cell (MSC)‐mediated immunosuppression, LTBP1 required for an adequate TGF‐β function, CD163, MR1 resulting in a relative increase in Tregs and TNFRSF1A required for STAT3 phosphorylation and MDSC accumulation . We also found that the expression of VEGFA, CCL2 and TGF‐β were restrained in the LGALS1 knockdown group.…”
Section: Discussionmentioning
confidence: 99%
“…This could, hypothetically, involve the blockade of a ‘beneficial’ inhibitory function of CTLA‐4 on T regs , or alternatively the triggering of the B7‐dependent immunomodulatory function of IDO in APCs . While recent evidence suggests that interference with the CTLA‐4 function on T regs depends upon the CTLA‐4 Ig dose , the study presented herein addressed the question whether IDO is triggered as immunomodulatory mechanism in APCs by belatacept.…”
Section: Discussionmentioning
confidence: 99%